DAPSONE INDUCED DRESS: A CASE REPORT - O, Balaji; D, Amita; George MM; K, Meena Kumari; A, Mohan Babu Vittalrao (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Drug reaction with eosinophilia and systemic symptoms. is a very dangerous adverse drug effect causing rashes, eosinophilia, and multiple organ damage. Many drugs are implicated in causing DRESS with most common ones being antimicrobials and antiepileptics. Dapsone used in the treatment of Hansen's disease as a first-line agent is known for causing many side effects ranging from nausea, vomiting, insomnia, anaphylaxis, hypersensitivity reactions, rashes, muscle weakness, abdominal pain, and so on. Hence, we report a rare case of dapsone-induced DRESS in a tertiary care hospital in South India. Â